Data Envelopment Analysis – A Key to the Museums’ ‘Secret Chamber’ of Marketing? - Lukáč, Michal; Mihálik, Jaroslav (Communication Today, 2018)
Intensive financial investments in marketing communication of museums are connected, in parallel, to their visual presentation as well as to strengthening the communication efficiency toward public. However, the unresolved question remains whether these finances are spent effectively or rather whether the communication strategy plan attracts the adequate target audience. How many visitors did react to a given campaign? Unfortunately, there is no single and definite answer on how to measure the efficiency of marketing communication in museums. The aim of the study is to use the Data Envelopment Analysis method to introduce a model for helpful assessment of the marketing communication efficiency within museums. While searching for the solution, we were inspired by the production economics, from which we chose the statistical method of Data Envelopment Analysis. This allowed us to evaluate the efficiency of production units and also to identify inefficiencies. In the public and non-profit sector, this methodological approach appears very rarely, and according to our findings, it has not been applied yet in the museum sphere in Slovakia.